Financial Literacy and Lifestyle in Shaping the Financial Behavior of Gen Z in Rangkasbitung, Lebak Regency - Furniawan Furniawan; D. Muhamad Yamin (Eduvest - Journal of Universal Studies, 2026)
A low understanding of long-term financial management and planning can lead to unwise financial decisions. The financial literacy of Gen Z in Rangkasbitung, lacking optimal access to formal financial education or accurate digital information, may face difficulties in managing finances wisely. This study aims to determine the effects of financial literacy and lifestyle on the financial behavior of Generation Z in Rangkasbitung, Lebak Regency. The research method used is quantitative, employing a survey approach through a questionnaire distributed to 100 respondents. Data analysis was conducted using the classical assumption test, multiple linear regression, correlation, partial test (t-test), and simultaneous test (F-test). The results of the study indicate that, partially, financial literacy has a significant effect on the financial behavior of Gen Z, and lifestyle also has a significant effect on financial behavior. Simultaneously, financial literacy and lifestyle have a significant effect on the financial behavior of Generation Z in Rangkasbitung. These findings emphasize the importance of improving understanding of financial literacy and lifestyle management to foster healthy financial behavior among the younger generation.